Cyanobacterial Diazotrophy and Earth’s Delayed Oxygenation - Olson, Stephanie L.; Reinhard, Christopher T.; Lyons, Timothy W. (Frontiers in Microbiology, 2016)
The redox landscape of Earth’s ocean-atmosphere system has changed dramatically throughout Earth history. Although Earth’s protracted oxygenation is undoubtedly the consequence of cyanobacterial oxygenic photosynthesis, the relationship between biological O2 production and Earth’s redox evolution remains poorly understood. Existing models for Earth’s oxygenation cannot adequately explain the nearly 2.5 billion year delay between the origin of oxygenic photosynthesis and the oxygenation of the deep ocean, in large part owing to major deficiencies in our understanding of the coevolution of O2 and Earth’s key biogeochemical cycles (e.g., the N cycle). For example, although possible links between O2 and N scarcity have been previously explored, the consequences of N2 limitation for net biological O2 production have not been examined thoroughly. Here, we revisit the prevailing view that N2 fixation has always been able to keep pace with P supply and discuss the possibility that bioavailable N, rather than P, limited export production for extended periods of Earth’s history. Based on the observation that diazotrophy occurs at the expense of oxygenesis in the modern ocean, we suggest that an N-limited biosphere may be inherently less oxygenic than a P-limited biosphere—and that cyanobacterial diazotrophy was a primary control on the timing and tempo of Earth’s oxygenation by modulating net biogenic O2 fluxes. We further hypothesize that negative feedbacks inhibit the transition between N and P limitation, with the implication that the pervasive accumulation of O2 in Earth’s ocean-atmosphere system may not have been an inevitable consequence of oxygenic photosynthesis by marine cyanobacteria.